Horabagrus melanosoma: a junior synonym of Horabagrus brachysoma (Teleostei: Horabagridae) - Ali, Anvar; Katwate, Unmesh; Philip, Siby; Dhaneesh, K. V.; Bijukumar, A.; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2014)
Horabagrus melanosoma was described from West Venpala in the lower reaches of the Manimala River, in the state of Kerala, India. It was distinguished from its nearest congener, H. brachysoma based on a combination of characters including darker body colour, shorter pelvic fin and greater number of anal fin rays. Examination of the type material revealed significant morphometric and meristic discrepancies with the original description. Based on multivariate morphometric, and genetic analysis of topotypical specimens, we propose that H. melanosoma should be treated as a junior synonym of H. brachysoma.